Hubungan Pengetahuan dengan Gangguan Pendengaran Akibat Penyemanan Pada Penyelam Tradisional di Kampus Bugis: Case Report - Zakiah Rahman; Devy Kurniawati; Riri Apriani (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
Occupation as a traditional diver has a very high risk of danger. The risk of working on a dive varies greatly depending on the type of dive being carried out. Perceived disorders include dizziness, bleeding, deafness, joint pain and excessive fatigue. The study aim to determine the relationship of knowledge with hearing loss due to diving in traditional divers in the Bugis village of Tanjung Pinang. The method used quantitative research with correlation design by means of consecutive sampling and sample size of 38 people. Data analysis using Chi Square. The results showed that there was a relationship of knowledge with hearing loss due to traditional dives with a p value of 0.046 (P <0.05), because diving activities were not equipped with knowledge about diving which had a long-term effect on the physiology of the human body such as hearing loss (Deafness) to divers. So that in the future traditional divers need to be given knowledge related to how to dive and the risks of traditional diving.Keywords: Knowledge, Divers, Hearing Loss